2013
DOI: 10.1105/tpc.113.113142
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence but Independent Biosynthesis of Catechyl and Guaiacyl/Syringyl Lignin Polymers in Seed Coats

Abstract: Lignins are phenylpropanoid polymers, derived from monolignols, commonly found in terrestrial plant secondary cell walls. We recently reported evidence of an unanticipated catechyl lignin homopolymer (C lignin) derived solely from caffeyl alcohol in the seed coats of several monocot and dicot plants. We previously identified plant seeds that possessed either C lignin or traditional guaiacyl/syringyl (G/S) lignins, but not both. Here, we identified several dicot plants (Euphorbiaceae and Cleomaceae) that produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
189
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(197 citation statements)
references
References 73 publications
7
189
1
Order By: Relevance
“…5E). It should be noted here that, as reported recently (Lan et al, 2016b), such HSQC NMR-based estimates of tricin concentrations most likely are excessive; tricin is mostly in lignins as the polymers' terminal units, and typical HSQC experiments overquantify such more mobile terminal units compared with rigid internal units (Mansfield et al, 2012;Tobimatsu et al, 2013;Okamura et al, 2016). In fact, a recent study reported that tricin concentrations in grass lignins determined by a more reliable chemical method are typically 1% to 3% (Lan et al, 2016b).…”
Section: Fnsii Mutant Rice Produces Cell Wall Lignins Devoid Of Tricinmentioning
confidence: 61%
See 2 more Smart Citations
“…5E). It should be noted here that, as reported recently (Lan et al, 2016b), such HSQC NMR-based estimates of tricin concentrations most likely are excessive; tricin is mostly in lignins as the polymers' terminal units, and typical HSQC experiments overquantify such more mobile terminal units compared with rigid internal units (Mansfield et al, 2012;Tobimatsu et al, 2013;Okamura et al, 2016). In fact, a recent study reported that tricin concentrations in grass lignins determined by a more reliable chemical method are typically 1% to 3% (Lan et al, 2016b).…”
Section: Fnsii Mutant Rice Produces Cell Wall Lignins Devoid Of Tricinmentioning
confidence: 61%
“…Manipulation of the canonical monolignol pathway had led to compositional alterations in the polymer due to the incorporation of nontraditional lignin monomers, such as caffeyl alcohol in a CCoAOMTdeficient plant (Wagner et al, 2011), 5-hydroxyconiferyl alcohol in CAldOMT-deficient plants (Jouanin et al, 2000;Ralph et al, 2001;Vanholme et al, 2010;Weng et al, 2010;Koshiba et al, 2013a), ferulic acid in CCRdeficient plants (Ralph et al, 2008;Wagner et al, 2013), and p-hydroxycinnamaldehydes in CAD-deficient plants (Kim et al, 2000;Marita et al, 2003;Sibout et al, 2005;Bouvier d'Yvoire et al, 2013;Koshiba et al, 2013b;Zhao et al, 2013;Anderson et al, 2015). Such malleability of lignification also is exemplified by the fact that numerous angiosperm plants produce seed coat-specific lignins derived from caffeyl and 5-hydroxyconiferyl alcohols (Chen et al, 2012Tobimatsu et al, 2013). Our discovery that FNSII deficiency in rice results in the As the quantity and quality of lignin affect many aspects of lignocellulosic biomass utilization, the regulation of lignin biosynthesis has been a primary target for cell wall bioengineering (Ragauskas et al, 2014;Beckham et al, 2016;Rinaldi et al, 2016).…”
Section: Fnsii Mutant Rice Incorporates Naringenin As a Novel Lignin mentioning
confidence: 99%
See 1 more Smart Citation
“…These factors perhaps explain why the use of DHP polymers has largely been limited to a number of excellent investigations into the biosynthesis [24][25][26][27][28][29] and biodegradation [30][31][32][33][34][35] of lignin rather than chemical depolymerisation. However this remains challenging and control over the relative distribution of linkages is lacking due to the reliance on a radical polymerisation process.…”
Section: -5mentioning
confidence: 99%
“…[1][2][3][4][5] Lignin has received great attention as a sustainable precursor for basic aromatic building blocks, such as phenols, which are currently obtained by synthetic chemistry from fossilbased feedstocks. [6][7][8][9] Lignin-a natural phenolic macromolecule present in vegetal cell walls comprising three kinds of phenylpropane units (as shown in Figure 1), namely guaiacyl alcohol (G), syringyl alcohol (S), and p-coumaryl alcohol (H) [10][11][12][13] accounts for 20-30 wt % of lignocellulosic biomass, 14,15 and it is a highly complex three-dimensional structured macromolecule in which large number of aromatic rings link together through CAOAC [16][17][18][19] and CAC bonds, 16,20 Figure 2. 16220 Aryl ether linkages can be more easily cleaved than the CAC linkages since the latter is stable and resistant to chemical depolymerization.…”
Section: Introductionmentioning
confidence: 99%